Identification of Risk Factors Associated with Nasopharyngeal Carcinoma (NPC) in the Pahang State of Malaysia Hospitals - Ahmad, Azmir; Basha, Muzaitul Akma Mustapa Kamal; Yassin, Wardah Mohd.; Rahman, Nor Azlina A.; Leman, Wan Ishlah; Rosla, Luqman; Yussof, Sharifah Nor Ezura Syed; Paul, Mark; Awang, Kamariah Mohamed; Abdullah, Kahari; Kaderi, Mohd. Arifin (Makara Journal of Health Research, 2022)
Background: Nasopharyngeal carcinoma (NPC) is the fifth most common cancer reported in Malaysia. Although several studies on NPC have been carried out, the risk factors associated with NPC in Malaysia are unknown. Therefore, this study was designed to investigate the risk factors associated with NPC cases in Pahang state. Methods: NPC cases that were diagnosed between 2012 and 2017 were recruited from two referral hospitals in Pahang. An interview was conducted using adapted questionnaires, which included demographic data, family history of cancer, and lifestyle. The data were analyzed statistically to identify the associations between the selected variables and NPC. Results: A total of 71 NPC cases and 81 control subjects were recruited from the hospitals. Multivariate analysis showed that a family history of NPC and current smoking were significantly associated with the risk of NPC (p < 0.05). Further analysis revealed a significant association between the risk of NPC in smokers with no family history of NPC (p < 0.05). Conclusions: This preliminary study suggests that family history and smoking are factors associated with the development of NPC in Pahang, which was consistent with previous studies.